Community-based practical behavioral intervention in public transportation for people with acquired brain injury: study of two cases using a single-case experimental design study. Issue 3 (4th May 2022) - Shimizu, Daisuke; Miyahara, Tomoko; Tanemura, Rumi
ABSTRACT: The purpose of this paper was to report on the progress of a behavioral approach to enable patients with acquired brain injury (age 57, male, stroke and age 36, old, female, TBI) using a community activity support center to commute alone using public transportation. In this study, two ABI patients were intervened to enable them to use public transportation. The frequency of intervention was once a month or once a week. The two community-dwelling adults each had post-ABI attention and memory deficits and anxiety. A-B-A single-case experimental design was employed for this study. The transportation route was stepped into multiple steps. Each step was scored in a unique way to determine the degree of assistance the participant received from others. This score was considered the main outcome. Tau-U analysis was used for statistical analysis. Statistically significant improvements in public transportation use were shown between baseline and intervention. There were no significant differences between the intervention and follow-up periods. The results suggest that behavioral interventions are beneficial in reacquiring the ability to use public transportation and that the intervention effects are sustained.